Comparison of male and female road cyclists under identical stage race conditions - Lim, A. C.; Peterman, J. E.; Turner. B. M.; Livingston, L. R. (Medicine & Science in Sports & Exercise, 2011)
Purpose: To compare the demands of a 6-d stage race using field measures of power output and HR in male (n = 8) and female (n = 10) competitive cyclists.